KELIMPAHAN POLEN DAN SPORA ENDAPAN CHANNEL DELTA MAHAKAM - -, Winantris (Fakultas Teknik Geologi Universitas Padjadjaran, 2012)
In the delta area there aretwo type of channelsnamely distributary channel and tidal channel. Both controlthe supply of sedimentforming thedelta. Channel is an open areaof vegetation.Channel justovergrown by plant water, but channel gets pollen and spore from the vegetation growing arround it. The aim of research is to know abundance of pollen and spore are deposted in the channel,to be usedas a guidedeposition environment and study provenance. The avarage pollen and spores in the sediment distributary channelat 47.73 grain per sampleincluded poor category and average pollen and spores in the tidal channel at 66.85 grain per sampleincluded in themoderately rich category. The abundance of pollen in the deposit of tidal channel is higher than deposit of distributary channel, while the abundance of fern sporeswere not significantly differentbetween the two channel.